Pretreatment of Reactive Dye from Textile Wastewater by Coagulation Technology - Siti Norsita, Mohd Rawi; Zularisam, A. W.; Mohd, Nasrullah; Wahidatul Azura Zainon, Najib (IRJET, 2016)
A physicochemical treatment was applied to study on removal of commercially used reactive dye and investigate the effectiveness of coagulation-flocculation from textile wastewater. Three types of coagulants were used like aluminium sulphate (alum), polyaluminium chloride (PAC), and magnesium chloride (MgCl2). Polyelectrolyte, Koaret PA 3230 was used as the coagulant aid. The coagulant dosage between 400 ppm to 5,000 ppm was studied using jar test. The changes of pH, types and dosage of coagulant, and the addition of coagulant aid on the percentage removal and the concentration of the dyes were determined through colour point. The results show that up to 90% colour removal for reactive dye could be achieved using alum of concentration 6,000 ppm and pH 2.4. Meanwhile, 99 % colour removal could be achieved using MgCl2with concentration of 4,000 ppm a nd pH 10.4, whereas 100% colour removal could be achieved using PAC with concentration of 2,000 ppm and pH 4.1. Among the coagulants used, PAC was the most effective coagulant in treating each dye, with the colour removal up to 100% at the dosage of 800 ppm. The flocs settling time for the treatment with MgCl2 was shorter than the treatment with PAC and the treatment with Alum was longer than the treatment with MgCl2 and PAC. This result can contribute some knowledge on the use of effective coagulants in treating textile industrial wastewater.